Validation of Integrated Pest Management Practices for Rice Insect in North-west Region of Bangladesh (Bangladesh Rice Journal, 2015)
Integrated Pest Management (IPM), developed by the Bangladesh Rice Research Institute (BRRI) for management of rice insect pests, was demonstrated and validated through intensive investigation in farmers fields of Pirganj and Taraganj in Rangpur district during 20122014 in two T. Aman and Boro seasons. A portion of each farmers field kept under the respective farmers supervision without any intervention, which was treated as control treatment (T4). The other portion was managed with three treatment combinations ie, T1=Prophylactic use of insecticide, T2=Perching + sweeping + need based insecticide application and T3=Perching only. BRRI dhan52 and BRRI dhan58 were used in Aman and Boro seasons respectively. RCB design was followed with eight replications for data analysis. The insect infestation was monitored fortnightly by visual counting from 20 hills and also 20 complete sweeps. The insect infestation, yield and yield contributing characteristics were analysed by one way analysis of variance by Tukeys post hoc test. The objective of this studies were to validate and demonstrate the IPM techniques in farmers' field. Yellow stem borer, rice leaf roller, long horned cricket, grasshopper, green leafhopper, brown planthopper, white-backed planthopper and gall midge were found as pests in both the locations. However, insect infestation was below the economic threshold level (ETL). No significant differences were observed for insect infestation among the treatments. Natural enemies eg, spider, ladybird beetle, dragon fly, damsel fly, carabid beetle and staphylinid beetle were noticed in both the locations. In some seasons and also locations some natural enemies were not found particularly where indiscriminate/continuous insecticide was used. Thus, it was indicated that indiscriminate/continuous use of insecticide has the detrimental effect on the population of natural enemies. Also, refrained from insecticide application at early crop stages (30-40-day after transplanting) natural enemy populations increased, which might reduce insect population below the ETL. Significantly lower yield was observed at farmers managed fields in both the locations. Therefore, it was found that indiscriminate/continuous use of insecticide had no effect on yield and yield contributing characters of rice, when insect infestation below the ETL. So, farmers could avoid continuous/indiscriminate use of insecticide, which might ultimately save production cost and the environment from insecticidal pollution as well.Bangladesh Rice j. 2015, 19(1): 17-31